A greener approach for impressive removal of As(iii)/As(v) from an ultra-low concentration using a highly efficient chitosan thiomer as a new adsorbent. Issue 69 (11th July 2016) - Singh, Prem; Chauhan, Kalpana; Priya, Vishal; Singhal, Rakesh Kumar
Abstract : Contamination of ground water with arsenic is a serious problem all over the world. Abstract : Contamination of ground water with arsenic is a serious problem all over the world. An urgent needs is being felt to develop a highly effective and extremely capable sorbent material for the removal of arsenic simultaneously in both species, i.e. As(iii ) and As(v ) from the contaminated water. But in natural water As(iii ) is present in a non-ionic form which causes a great challenge to remove As(iii ) as compared to As(v ) especially at a relatively low concentration. In this context the green chitosan thiomers with a high density of strong arsenic chelating (–SH) groups have been developed via thiourea reagent under conventional and microwave conditions and have been employed for the removal of As(iii ) and As(v ). The sorption study supported almost identical sorption amounts of 17.0 and 17.6 mg g −1 at 50 ppb for As(iii ) and As(v ) via the thiomer, respectively. The synthesized chitosan thiomer even proved efficient in sorption of As(iii ) and As(v ) at 10 ppb and purified water below the WHO prescribed detection limit. Moreover, the thiomer can be used for arsenic removal without any pH adjustment in the pH range of 6.0 to 9.0, which is in accordance with the pH of natural water. The As(iii ) and As(v ) sorption mechanism on the surface of chitosan thiomer has also been confirmed by FTIR, Raman, XPS and cyclic voltammetry. Isotherm studies indicated that the Freundlich model is successful in describing the adsorption process to a better extent than the Langmuir model for the As(iii ) and As(v ) adsorption on the chitosan thiomer. In the kinetic studies the pseudo second-order kinetic model supported the kinetic data best. The intraparticle diffusion study suggested that both external mass transfer and intraparticle diffusion steps contribute to the rate controlling step. Thus, the proposed solution for arsenic removal is simple, promising and economical which needs no pre and post treatment in natural water samples even at the ppb level.